â€œQuality Audit of Finished Productsâ€ - Patel, Ankit (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT The purpose of self-inspection is to evaluate the manufacturerâ€™s compliance with GMP in all aspects of production and quality control. The self inspection programme should be designed to detect any shortcomings in the implementation of GMP and to recommend the necessary corrective actions. Self-inspections should be performed routinely, and may be, in addition, performed on special occasions, e.g. in the case of product recalls or repeated rejections, or when an inspection by the health authorities is announced. The team responsible for self-inspection should consist of personnel who can evaluate the implementation of GMP objectively. All recommendations for corrective action should be implemented [5].